Design of mobile application for communication and user interface of ESP32 potentiostat system - Supriyanti, Retno; Widanarto, Wahyu; Dwi Susanto, Putra; Ardi Wicaksono, Madya; Rais Akhdan, Syafrudin; Alqaaf, Muhammad (Institute of Advanced Engineering and Science, 2025)
The potentiostat utilizing the ESP32 has a 12-bit analog-to-digital converter (ADC), meaning the maximum value for ADC voltage readings on the ESP32 is 4095. These ADC readings are then converted into actual voltage units, ensuring more accurate measurements on the potentiostat. To facilitate the use of the ESP32 potentiostat, a mobile application must be designed as a user interface for data communication. The application will be developed on a mobile platform using a Bluetooth low energy (BLE) communication channel for easier access. The development process will utilize visual studio code as the code editor and programming languages like Dart and Flutter. The resulting application will feature a user-friendly dashboard, display data in a cyclic voltammetry graph, and store data in comma-separated values (CSV) files or images in the phone’s memory. This stored data will simplify observing results obtained from the ESP32 potentiostat.